1985
DOI: 10.1021/jf00061a026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light on the organophosphorus pesticides bromophos and iodofenphos and their main degradation products examined in rainwater and on soil surface in a long-term study

Abstract: The photolysis of bromophos [ , -dimethyl 0-(4-bromo-2,5-dichlorophenyl) phosphorothioate], iodofenphos [ , -dimethyl 0-(2,5-dichloro-4-iodophenyl) phosphorothioate], and their main degradation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The results also indicated that the hydrolysis of the pesticide may involve two different mechanisms, depending on the nature of the exchangeable cations. Allmaier and Schmid (1985) studied the fate of bromophos and iodofenphos and their major metabolites in the environment and found that photodecomposition was a major contributor to their hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The results also indicated that the hydrolysis of the pesticide may involve two different mechanisms, depending on the nature of the exchangeable cations. Allmaier and Schmid (1985) studied the fate of bromophos and iodofenphos and their major metabolites in the environment and found that photodecomposition was a major contributor to their hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of bromophenols may also enter the environment. Some, such as tetrabromobisphenol-A [2,2-bis-(3,5-dibromo-4-hydroxyphenyl)propane] and tetrabromo-o-cresol are used as commercial products, while others are used as pesticides and herbicides or may be produced through abiotic hydrolysis of the original insecticide, e.g., bromophos [0,0-dimethyl-O-(4-bromo-2,5-dichlorophenyl)-phosphorothioate] (3). In addition, bromophenols may be produced during the chlorination of water containing bromide and phenolic compounds (47).…”
mentioning
confidence: 99%
“…Involvement of photolysis in field dissipation of organochlorine pesticides including (122) and (123) was demonstrated by monitoring studies in 99 fields (Suzuki and Yamato 1974). Degradation of bromophos (140) and iodofenphos (141) on soil was slightly enhanced by sunlight irradiation via cleavage of the p-o aryl bonds (Allmaier and Schmid 1985;Allmaier et al 1984). Less photoreactivity of dicofol (133) was briefly reported on soil (EPA OPPTS 1998d).…”
Section: T Katagimentioning
confidence: 99%